THE ROLE OF MUSIC VIDEOS IN UZBEK CULTURE - Anvar Juraevich Adilov (Galaxy International Interdisciplinary Research Journal, 2024)
In this scientific article, in the process of analyzing young people working in Uzbek show business today, and in the process of analyzing the music videos they create, their achievements and problems are studied, and the necessary suggestions and comments are provided. At the same time, the work of young music video directors and currently working cameramen will be examined. The article objectively highlights the role and significance of clips created in our country, based on the principles, skills, scientific and technical possibilities of interaction between the work of the operator in Uzbek video clips and artistic creativity. After analyzing on a scientific basis the causes of these shortcomings and the current state of youth creativity in Uzbek show business, proposals and comments are made to eliminate the existing problems of creative cooperation.